High tough W-added silicon nitride ceramics. Issue 15 (15th October 2019) - Wang, Lujie; Qi, Qian; Zhang, Hui; Yang, Xiao; Liu, Zehua; Ge, Sheng; Peng, Xinglin; Liu, Xuejian; Huang, Zhengren
Abstract: Silicon nitride ceramics with varying amounts of tungsten were fabricated by sintering with various nitrogen pressure using yttria and alumina as sintering aids. It has been found that the chemical composition of the ceramics is sensitive to the nitrogen pressure during the sintering process, and the adverse interfacial reactions between W and Si3 N4 could be perfectly inhibited by altering nitrogen pressure. The weak interfacial bonding strength between the tungsten particle and silicon nitride matrix dramatically promotes crack deflection, branch and grain pullout during the fracture process. As a consequence, with increasing W fraction, the fracture toughness of silicon nitride ceramics increases noticeably. Nevertheless, excessive W fraction lowers the relative density and degrades the performance of the ceramics. The silicon nitride ceramics with high fracture toughness about 11 MPa m 1/2 and high flexural strength about 1 GPa were fabricated.